2022
DOI: 10.3390/biology11091300
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Texture of the Mineral Matter in the Bivalve Shells of Gryphaea dilatata Sowerby, 1816

Abstract: It is assumed that the crystallographic texture of minerals in the shells of recent and fossil mollusks is very stable. To check this, it is necessary to examine the shells of animals that had lain in sediments for millions of years and lived in different conditions. It is revealed that the crystallographic texture of calcite in the shells of Gryphaea dilatata from deposits from the Middle Callovian–Lower Oxfordian (Jurassic), which lived in different water areas, is not affected by habitat conditions and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The pole figure measurements have been developed for metals and alloys [22,23]. At present, there is a great interest in the crystallographic texture study of biological samples [24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pole figure measurements have been developed for metals and alloys [22,23]. At present, there is a great interest in the crystallographic texture study of biological samples [24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that the crystallographic texture of calcite and aragonite in the shells of bivalve mollusks is very stable over time [30,32], in different parts of the habitat under different climatic conditions [34], and under the influence of trace elements [35]. Some objects showed unusually high sharpness of crystallographic texture [30,33].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetically and physiologically informative tissues were probed by synchrotron [ 34 ] to support the previous identification of reproductive tissues in dinosaurs [ 35 , 36 ]. Technologies continue to broaden not only the type of questions to be asked, but the type of fossils we can analyze, from coprolites [ 33 ], teeth [ 37 ], and invertebrates [ 22 , 38 , 39 ] to dinosaurs [ 25 , 34 , 40 , 41 , 42 , 43 , 44 ], mammals [ 45 ], and our own lineage [ 29 , 32 , 46 ].…”
mentioning
confidence: 99%